Moving away from depression: Physical activity changes in patients undergoing r-TMS for major depressive disorder. (March 2019) - Fagan, Matthew James; Faulkner, Guy; Duncan, Markus; Yun, Lira; Blumberger, Daniel; Daskalakis, Zafiris J.; Downar, Jonathan; Vila-Rodriguez, Fidel
Abstract: Background: Physical activity (PA) may predict or mark successful treatment from major depressive disorder after repeated-transcranial magnetic stimulation (r-TMS). Objectives: To explore if r-TMS treatment responders were more physically active than non-responders at baseline, and to determine if treatment responders increased PA compared to non-responders post-treatment. Methods: Thirty subjects were included in the study. PA was measured through Actical accelerometers. Baseline PA levels were compared through separate independent t-tests, whereas post-treatment changes were compared through separate ANCOVAs. Results: There were no differences in PA at baseline between groups. Controlling for baseline PA levels, ANCOVAs identified a non-significant treatment effect between moderate-to-vigorous physical activity levels post-treatment between groups [ p = 0.276, η 2 = 0.044]. A significant treatment effect was found between groups for light physical activity favouring responders [ p = 0.009, η 2 = 0.226]. Conclusion: Responders' LPA significantly increased in comparison to non-responders receiving r-TMS for major depressive disorder. Highlights: Responders to treatment increased light physical activity. Increases in light physical activity may be a marker of r-TMS treatment success. Assessing physical activity during depression treatment is recommended.